KOREKSI ANGGAPAN BAZAAR ECONOMY, ORDER DAN REGULATION THEORY PADA ORIENTASI USAHA PKL KOTA SURAKARTA PASCA KRISIS MONETER - Joko Suwandi (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2013)
The particular objective of this research is to describe the orientation shift trend of vendor sellers business in Surakarta city prior, during and post the monetary crisis in order to obtain rectification of Bazaar Economy of Clifford Geertz, and Order Theory and Regulation Theory of Evers. H.D. This qualitative research of case study tried to describe the condition, activity and the development of vendor sellers’ orientation in Surakarta before (1997), during (1997 to 2004) and after monetary crisis (2004-recently) occurred in Indonesia, particularly in Surakarta city. The place of the research is in Surakarta city with the following data source; vendor sellers with all their activities, all the former public officials and officials associated to vendor sellers during and after the monetary crisis. The participants are selected through purposive sampling integrated with snowball sampling using key informant. The data are analyzed using interactive analysis from Miles and Huberman, through three stages activity namely, data reduction, data display, and conclusion drawing/verification. The conclusions of this research are as follows; 1) the vendor sellers’ orientation prior and during the monetary crisis comply to the informal sectors characteristics according to Clifford Geertz’s Bazaar Economy and Order Theory and Regulation Theory of Hans-Dieter Evers but the characteristics on post-monetary crisis have altered; 2) The vendor sellers’ characteristics after the monetary crisis can be classified into two namely the static group and dynamic group. The first group is dominated by vendor sellers, who have capital, management limitation and their business as subsistence. The later group is dominated by vendor sellers who have big capital, administered using modern management and have become the business to increase welfare. The inclination of orientation shift of vendor sellers in Surakarta city is developing slowly and developmental.